Navigating the digital frontier: Challenges and solutions for Dajia Insurance Group Limited Liability Company in the era of digital transformation - Yonghui, Wu (Nurture, 2025)
Purpose: This paper discusses Dajia Insurance Group’s limited liability company (Dajia Insurance) challenges and solutions in the digital transformation environment. Businesses, including insurance organizations, are adopting digital due to rapid technological developments and changing consumer preferences to be competitive and relevant. However, Dajia Insurance faces unique challenges in the insurance industry and its operations. Design/Methodology/Approach: The analysis begins with identifying the key challenges Dajia Insurance faced during its digital transformation journey, including outdated legacy systems and processes, cultural resistance and talent acquisition. These challenges reveal severe corporate constraints that hinder the company's embrace of digital technologies. The study also considers external factors such as regulatory compliance and market realities that constrain Dajia Insurance’s approach to digitization. This paper provides practical recommendations tailored to Dajia Insurance's needs and circumstances based on industry best practices and case studies. Findings: The study proposes several solutions to overcome the limitations and create new opportunities for Dajia Insurance in the digital age. This includes investments in modern infrastructure, access to innovative workers and fostering the right relationships with technology start-ups and suppliers. Additionally, the importance of active engagement with regulators and adopting a customer-centric approach to product and service offerings is highlighted. Practical Implications: The solutions seek to help Dajia Insurance overcome the challenges of digital transformation and reap the benefits of digital technology, such as higher operational efficiency, improved customer experience, and, ultimately, long-term digital success in a growing economy. This paper presents a comprehensive strategy for Dajia Insurance to successfully cross the digital frontier with specific solutions to overcome obstacles and exploit the opportunities offered by digital transformation.